STRUCTURAL ANALYSIS FOR WEIGHT OPTIMIZATION OF MACHINE TOOL BED - Gururaj Deshpande; S.T. Jagtap; A.I. Ambesange (International Journal of Innovations in Engineering Research and Technology, 2021)
With the increasing pace in the industrial and technological developments there is a phenomenal change in the trend of machine tool development that brings to the fore, the modern production requirements like higher speeds, closer tolerances and accuracy. The performance of a machine tool depends primarily upon the static and dynamic behavior of the basic structure. In the present day structural engineering, the designing of the machine tools to have high stiffness with optimum use of materials to its fullestcapability.Machine tool structures have been analyzed in the past to study and improve their rigidity using several methods like Analytical Methods, Strength of materials methods, Elasticity methods and simulation methods using packages. Under simulation method use of Finite Element Analysis has become one of the most powerful and popular tool for structural analysis. The same could be used in the analysis of machine tool.The performance of machine tool depends upon the static and dynamic behavior of the basic machine structure. The bed structure has to resist the deformations caused by the weight of the moving part of the machine and cutting forces. The machine tool must be made up of proper material with high static and dynamic stiffness to resist thedeformations. In the present investigation structural analysis of the CNC machine tool main bed for weight optimization is carried out using FEA commercial package ANSYS 10.0. Modal analysis was carried out to determine the natural frequency to verify stiffness of the bed.